2016
DOI: 10.1039/c6ra17327f
|View full text |Cite
|
Sign up to set email alerts
|

Injectable and self-healing dynamic hydrogel containing bioactive glass nanoparticles as a potential biomaterial for bone regeneration

Abstract: Combination of Au-based dynamic hydrogel with 100 nm bioactive glass nanoparticles resulted in the formation of an injectable, self-healing and biocompatible hydrogel nanocomposites with osteoinductive properties and potential for bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Soft CANs are excellent candidates as long‐term tissue replacements, as demonstrated by gold–thiolate and disulfide crosslinks in an artificial nucleus pulposus hydrogel that recapitulated of the biomechanical characteristics of healthy intervertebral discs 97. Additionally, similar CANs were used in a network containing agglomerates of bioactive glass nanoparticles as a scaffold for in situ bone regeneration 98. Other synthetic and natural polymers have been modified with dynamic imine and thiol–aldehyde crosslinks and supplemented with bioactive compounds, offering a variety of approaches to adaptable in vivo scaffolds for osteochondral defect repair and regeneration.…”
Section: Enabling Features and Emerging Applications Of Cansmentioning
confidence: 99%
“…Soft CANs are excellent candidates as long‐term tissue replacements, as demonstrated by gold–thiolate and disulfide crosslinks in an artificial nucleus pulposus hydrogel that recapitulated of the biomechanical characteristics of healthy intervertebral discs 97. Additionally, similar CANs were used in a network containing agglomerates of bioactive glass nanoparticles as a scaffold for in situ bone regeneration 98. Other synthetic and natural polymers have been modified with dynamic imine and thiol–aldehyde crosslinks and supplemented with bioactive compounds, offering a variety of approaches to adaptable in vivo scaffolds for osteochondral defect repair and regeneration.…”
Section: Enabling Features and Emerging Applications Of Cansmentioning
confidence: 99%
“…Ideally, an injectable hydrogel should perform as a low-viscosity liquid through application, but as an elastic solid when filling the defect with a fast conversion between both the states [43]. Viscoelasticity of the injectable hydrogels was evaluated using dynamic frequency test to measure the elastic (G ), viscous (G ) and complex shear (G * ) moduli, which are shown in figure 6.…”
Section: Viscoelastic Behaviour Studiesmentioning
confidence: 99%
“…Hydrogel–Particle Mixtures : In addition to their use as colloidal building blocks or crosslinkers, nanoparticles can also be incorporated into polymeric hydrogels for mechanical reinforcement or other types of functionalization without affecting the self‐healing behavior of the polymeric hydrogel . This approach has been employed by Gantar et al to produce injectable and self‐healing gels for bone regeneration. This study showed that clusters of bioactive glass nanoparticles could effectively reinforce a dynamic hydrogel matrix composed of gold‐containing 4‐arm thiol‐terminated PEG, resulting in the formation of composite gels that were bioactive (apatite‐forming) and self‐healing.…”
Section: Intrinsic Self‐healing Biomaterialsmentioning
confidence: 99%